Study of rock slope stability for formation outcrops in limb north eastern poor anticline North Iraq - Mohammad. R. Abood; Amera. I. Hussein; Marwan. A. Marhon (Tikrit Journal of Pure Science, 2023)
This Study aims at rock Slopes Stability for formation in limb northـeastern poor anticline (Fatha, Injana and Mukdadyah). In (5) Stations, representing all types of failures (taken place and possible). General Survey for rock Slopes included Classification and engineering description according to [1][2]. The slopes in the area are Classified based on the direction of the Strike Slopes and Strike of  beds into Parallel and Oblique Lateral Slopes according to [3] Classification and the Slope Types are Concordant Slope and discordant Slope.